Defining the boundaries: the implementation of health and social care policies for adults with learning disabilities - Fyson, Rachel (2002)
This thesis examines why community care policies for adults with learning disabilities have proved so hard to implement in a sustained, equitable manner, and explores the apparent chasm between official policy and actual practice in the light of current theories of social policy implementation. It focuses specifically on the relationship between health and social services, and investigates the factors which affect the ability of these agencies to co-operate effectively in the provision of services to this client group.